Flow in Inclined Thin Liquid Films with no Inertia Force - Joseph Abdel-Ahd; Hikmat Mustafa; Khidr Khidr (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper we have investigated viscous flow in symmetric thin liquid films which are inclined by an inclination angle  to the horizontal for an incompressible liquids in two dimensions with no inertia force. We use the (Navier-Stocks) equations and we obtain equations that govern such flow and we solved these equations by numerical methods to obtain the thickness of the film.